Clinical Features and Surgical Outcomes of the Children With Urolithiasis at a Tertiary Care Hospital: First Report From Somalia - Eraslan, Aşir; Mohamed, Abdikarim Hussein; Cimen, Sertac (Frontiers in Pediatrics, 2022)
Introduction: There are very few studies regarding pediatric urolithiasis (PU) reported from Africa, and to date, no data have been presented from Somalia. This study evaluated the sociodemographic and clinical characteristics and surgical outcomes of PU patients treated at Somalia's only tertiary care center. Method: The data of all patients diagnosed with urolithiasis during a 6-year period were reviewed. Only pediatric (age<18) urolithiasis patients were included. Demographic parameters, clinical features including stone characteristics, radiological findings, and surgical outcomes were analyzed. Results: Overall, 227 (127 male, 100 female) patients were included. The rate of PU was 8.1%. The mean patient age was 12.7±3.2. More than two-thirds of the patients (n=161, 70.9%) were adolescents. The stones were located in the kidney in 50.7%, the ureter in 33%, and the bladder in 14.5%. Distal ureteral stones (36%) accounted for the majority of ureteral stones, followed by the ureterovesical junction (26.7%) and proximal ureteral (24%) stones. The mean stone size was 16.2 mm. Most (42.3%) stones had a 10-20 mm diameter, while 23.3% were sized between 6-10 mm. Renal insufficiency was present in 5.3%. Among 227 patients, 101 (44.5%) underwent minimally invasive procedures including ureterorenoscopic lithotripsy (n=40, 18%), retrograde intrarenal surgery (n=30, 13.2%) and percutaneous nephrolithotomy (n=31, 14%). Open pyelolithotomy was the most common surgery performed (n=53, 22.3%). Surgical site infection developed following 3.5% of the open surgery cases. The stone-free rate was 91.3%. It was significantly higher in open cases (98%) compared to the cases performed via a minimally invasive approach (83%)(p=0.02). Conclusion: In Somalia, PU is more common than in many other countries. Open surgery continues to be the primary treatment modality for children with urolithiasis due to the restricted endourology resources. However, minimally invasive approaches have evolved over the last years.